Asymmetric palatine tonsil in a pediatric patient: Is it always a malignant neoplasm? - Alejandro Azamar; Carlos De la Torre-González; Luis Juárez-Villegas; Stanislaw Sadowinski-Pine; Hiram Álvarez-Neri (Permanyer, 2021)
Background: A relatively frequent clinical finding in children is an asymmetric tonsil, which can have multiple etiological possibilities, including a malignant disease. The clinical finding of tonsillar asymmetry is found in approximately 2% of the pediatric population. The incidence of malignancy in the tonsils is low, estimated as 2.5 cases per 10,000 tonsillectomies. Due to its low incidence, the diagnostic tonsillectomy is not justified when tonsillar asymmetry is the only clinical finding. However, it is necessary to identify the critical clinical findings of high suspicion of malignancy that justify the performance of immediate surgery in the pediatric population. Case report: We present the case of a 10-year-old male patient. Four months before admission, the patient started with pharyngodynia and dysphagia, treated as recurrent tonsillitis. Due to exacerbation of the symptoms, orthopnea, and B symptoms, the patient came to consultation; tonsillar asymmetry was observed predominantly on the left side, with exophytic lesions extending to the hypopharynx. We decided to perform an incisional biopsy and tracheostomy due to compromised airway; histopathological diagnosis came back as B-cell lymphoma. Conclusions: Given the clinical scenario of recurrent tonsillitis, unresponsive to conventional medical treatment with antibiotics, tonsillar asymmetry with suspicious tonsillar appearance accompanied by symptoms such as fever, diaphoresis, cervical lymphadenopathy, obstructive symptoms in a pediatric patient, it is necessary to refer the patient to the specialist for timely diagnosis and treatment.